The Use of Language Politeness to Increase Student’s Academic Motivation and Self-Regulated Learning - Yusri, Yusri (Universitas Negeri Makassar, 2023)
Abstract. The purpose of this study was to examine the impact of applying the theory of language politeness as the instruction medium in increasing academic the motivation and self-regulated learning of students, especially in the writing class. This is a quantitative study with an experimental approach. This study only involved one experimental group without the control group as a comparison. The participants in this study were 25 students of the foreign language department who took writing course. Data collection techniques consisted of questionnaires, interviews, and observations. The data analysis technique consisted of descriptive and inferential statistics in the form of a paired sample t-test. The results of the comparison of pre-test and post-test data using the paired sample t-test showed that the significance value (0,000) was smaller than the standard value of the significance value (0.05). This proves that the use of politeness theory of language as the language of instruction in the process of learning could increase student academic motivation and self-regulated learning.Keywords: Academic Motivation, Self-Regulated Learning, Language Decency Theory, Teaching Foreign Language